Evaluation of potentially inappropriate medication in older patients with cardiovascular diseases—STOPP/START-based study - Krustev, Tzvetan; Milushewa, Petya; Tachkov, Konstantin; Mitov, Konstantin; Petrova, Guenka (Frontiers in Public Health, 2022)
Objective: This study aims to evaluate the use of STOPP/START criteria in the identification of potentially inappropriate medications and potential prescribing omissions in elderly patients with cardiovascular diseases in Bulgaria. Materials and methods: A prospective, questionnaire-based study was conducted among 543 elderly patients across 25 pharmacies. Socio-demographic characteristic, disease profile, symptoms, and medication data were collected. The questionnaire was developed for the purposes of the EUROAGEISM project. Out of all 543 patients, only those with documented cardio-vascular diseases were extracted and the medication profile per patient was evaluated for potentially inappropriate medications (PIMs) and potentially prescribing omissions (PPOs) using STOPP/START criteria version 2. In addition, several risks for potentially inappropriate prescribing were calculated with the focus being on the Odds and Risks to develop a PIP. Results: 428 from 531 patients with cardiovascular diseases (CVDs) were included in the analysis of PIP (40.52% aged 65-69 years, 61.88% female, 64% had up to 6 comorbidities, and 21.72% presenting with polypharmacy). A total of 71 PIMs in 64 patients with polypharmacy were identified applying STOPP criteria. 56% of patients taking above five medicines daily had PIMs. The majority of PIMs (31%) were related to CVDs treatment, followed by PIMs in the treatment of endocrine diseases (22.54%), duplication of medicines (8.46%), etc. 44 PPOs were identified with START criteria. 22.72% were related to lack of proton pump inhibitors (PPI) in the presence of gastroesophageal disorders, and the same percentage was for lack of Calcium-vitamin D supplementation. Applying the methodology of risks calculation the sample risk for PPO was 2.1% and for PIМ 3.4%. At sample level the relative risk for PPO was 62% out of the risk for PIM and at population level varied between 42.8% - 89.8%. Conclusion: Application of methodologies for detection of potentially inappropriate prescribing is not part of routine clinical practice in Bulgaria. Our study demonstrates a high percentage of potentially inappropriate medication among elderly patients with polypharmacy. Along with the ageing population in Bulgaria, economic burden of polypharmacy and the prevalence of cardiovascular diseases, it is especially important to gain deep understanding of address potentially inappropriate medication use.